Effects of 8 Weeks of Balance or Weight Training for the Independently Living Elderly on the Outcomes of Induced Slips - Kim, Sukwon (2010)
The study was conducted to evaluate if balance or weight training could alter gait characteristics of older adults contributing to a reduction in the likelihood of slip-induced falls. A total of 18 older adults were evaluated for the study. The results indicated decreases in heel contact velocities and the friction demand characteristics after eight weeks of training although fundamental gait characteristics such as walking velocity and step length were not changed. The results also indicated an increase in transitional acceleration of the whole body center of mass. The number of falls after eight weeks was reduced in training groups. These findings were found in conjunction with the improvements in knee flexor muscle and plantarflexor muscle strength. In conclusion, after training, older adults were less likely to initiate slips and more likely to recover from slips.